Efficient Gamma‐Retroviral Transduction of Primary Human Skin Cells Using the EF‐c Peptide as a Transduction Enhancer. Issue 1 (27th January 2022) - Barbier, Martin A.; Piaceski, Angela Dakiw; Larouche, Danielle; Villeneuve, Sarah H.; Ghani, Karim; Pope, Elena; Caruso, Manuel; Germain, Lucie
Abstract: Efficient gene transfer into cultured fibroblasts and keratinocytes during retroviral transduction is a critical step toward the treatment of genodermatoses such as epidermolysis bullosa. However, achieving high transduction rates is still a difficult task, particularly for the insertion of large coding sequences for which high viral titers cannot always be obtained. Multiple polycationic molecules, such as polybrene, which has been used in several clinical trials, have the ability to boost ex vivo retroviral gene transfer. However, the use of polybrene has been associated with a reduction of the proliferation and growth potential of human keratinocytes in culture. We developed a method for the efficient retroviral transduction of primary fibroblasts and keratinocytes using EF‐c, a polycationic nanofibril‐forming peptide. In comparison with polybrene, we found that the retroviral transduction efficiency with EF‐c was increased 2.5‐ to 3.2‐fold for fibroblasts, but not for keratinocytes. Moreover, the use of EF‐c did not affect fibroblast proliferation and keratinocyte stem cell content, whereas polybrene induced a decrease in both. This method could have a positive impact on the development of ex vivo gene correction of genodermatoses, allowing for more efficient gene transfer into primary skin cells with little to no effect on proliferation and stem cell content. © 2022 Wiley Periodicals LLC. Basic Protocol : Fibroblast and keratinocyte transduction Support Protocol : Assessment of transduction efficiency through flow cytometry analysis